Semantic interpretation of the qur’anic concept of politics: its relevance to Nigeria situation (2012)
A lot of theories had been propounded by early and modem philosophers in order to have a suitable, stable and desirable political industry in Africa and the world at large. Such include Thomas Hobbes’s concept of political representation or individualization and modem democracy, John Locke’s theory of state of nature and social contract, Ibn Khaldun’s theory of As-Sabiyyah (Solidarity) and yet the Realists, Liberals and Radicals were unable to supply a perfect model. Some scholars clamour that religion, gender discrimination and racial identity should be detached from the politics for its sustainability yet, their efforts have not yielded deserved results. The penetrating dynamism of the Qur’àn is tremendous and irresistible, the practicability of its teachings are far all the ages. Therefore the paper examines the dictates of the Qur'an, whose universality is encompassing irrespective of race, gender and religion. Its concept of Politics, Election/Selection of a leader and Electorate could be a model to be adopted to the present nature of Nigeria politics as described by scholars and the adoption of this Qur’anic model might proffer permanent solution for stability, suitability and desirability of political industry in Africa and world at large.